DIFFERENCES IN STUDENT READINESS USING ANIMATED VIDEOS ABOUT FIRST AID ABOUT BURNS - Usnawiyah, Usnawiyah; darotin, rida (LPPM Universitas dr. Soebandi, 2025)
Background: Burns often become a serious problem if they are treated incorrectly. Be it light burns, moderate burns or severe burns. Proper handling of burns is very important at the start of the burn incident, whereas many people and school children currently treat burns incorrectly. Purpose: To determine the difference in students’ readiness before and after being given health education using an animated videos of first aid burns using animated videos. Methods: In this research the author used a quantitative method, one group pretest-posttest design system approach. Researchers involved 35 students at SMPN 2 Krucil with 32 sample. The technique used purposive sampling. Then the media instruments used were questionnaire sheets and analysis using the Wilcoxon test (non-parametric). Results: Students' readiness before being given the animated video was in the least ready category, namely 27 respondents (84.4), and after being given the animated video, it was in the very ready category, the highest was 23 respondents (71.9%). From the Wilcoxon analysis, it was found that p (0.00) < α (0.05), so it can be concluded that H0 was rejected while Ha was accepted. Conclusions: There was a difference in readiness between students before and after being given health education using an animated video about first aid for burns. Discussion: It is hoped that educational institutions can provide material regarding first aid for burns to students using animated videos to increase students' readiness in dealing with first aid for burns which can occur at any time